The emergence of teacher self in the elementary classroom. (April 2023) - Cole, Chelsea; Pinnegar, Stefinee; Newberry, Melissa; Cutri, Ramona; Smith, Leigh
Abstract: Significant research and ongoing inquiry highlight the importance of understanding and recognizing the development of identities and beliefs among teachers. These studies use techniques of reflection on the past or present to elucidate the developmental process of teacher identities and beliefs and their impact on the profession. Based on this research, the development of teacher identities and beliefs commence during childhood. Yet studies have depended on reflection rather than the actual accounts children provide concerning their emerging development of teacher identities and beliefs from their perspective. This study uses qualitative methods. Through the analysis of focus groups and individual interviews findings about the identities and beliefs held by fifth-grade students who plan to become teachers emerged. Revealing the early developing identities of future teachers provides necessary insight into the emerging curricular needs of teacher education programs.